2022
DOI: 10.3390/ijerph19127123
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Vaccine Hesitancy among Health Care Workers during the COVID-19 Pandemic

Abstract: Most studies of COVID-19 vaccine hesitancy among health care workers (HCWs) have been descriptive, few have tested models to predict hesitancy, and none have examined the possible relationship between HCWs’ distress and vaccine hesitancy. This study examined predictors of COVID-19 vaccine hesitancy, including HCWs’ distress after taking into account HCW sex, doctoral-level status, race, age, and exposure to COVID-19. Further, it examined specific reasons HCWs endorsed for their hesitancy. 266 HCWs in the Unite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Strategies tailored to specific populations and concerns, when combined with other interventions, such as incentives or reminders, are highly effective in addressing vaccine hesitancy. 36 , 37 Vaccination mandates have proven to be the most impactful intervention for increasing SIV among HCWs. 38 In Switzerland, unlike some countries, there are no mandatory vaccines, and many HCWs are opposed to mandatory vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies tailored to specific populations and concerns, when combined with other interventions, such as incentives or reminders, are highly effective in addressing vaccine hesitancy. 36 , 37 Vaccination mandates have proven to be the most impactful intervention for increasing SIV among HCWs. 38 In Switzerland, unlike some countries, there are no mandatory vaccines, and many HCWs are opposed to mandatory vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Even though EE was present in one-third of the sample and high DP and low PA were present in approximately half of the sample, these factors were not signi cantly associated with acceptance of annual COVID-19 booster vaccination. A survey conducted in the United States also revealed that stress has no effect on COVID-19 vaccine hesitancy [43]. Bivariate analysis revealed that those who reported higher burnout levels for the three subscales were more likely to be hesitant to receive an annual booster, though this was not statistically signi cant.…”
Section: Discussionmentioning
confidence: 96%
“…Most research on COVID-19 vaccine hesitancy among HCWs has been conducted in high-income countries [ 9 , 10 , 11 , 12 , 13 , 14 ]. Studies in Africa, many of which were undertaken prior to the availability of vaccines, revealed mixed responses to the impending availability of vaccines.…”
Section: Introductionmentioning
confidence: 99%